2019
DOI: 10.1080/09513590.2019.1645110
|View full text |Cite
|
Sign up to set email alerts
|

A Phase III randomized controlled trial of oral dydrogesterone versus intravaginal progesterone gel for luteal phase support in in vitro fertilization (Lotus II): results from the Chinese mainland subpopulation

Abstract: Lotus II, a randomized, open-label, multicenter, international study compared the efficacy and safety of oral dydrogesterone versus micronized vaginal progesterone (MVP) gel for luteal support in IVF. A prespecified subgroup analysis was performed on 239 Chinese mainland subjects from the overall study population (n ¼ 1034), who were randomized to oral dydrogesterone 30 mg or 8% MVP gel 90 mg daily from the day of oocyte retrieval until 12 weeks of gestation. The aim was to demonstrate non-inferiority of oral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
(55 reference statements)
0
5
0
Order By: Relevance
“…Finally, six RCT (Chan et al, 2021;El-Zibdeh, 2005;El-Zibdeh and Yousef, 2009;Griesinger et al, 2018;Pandian, 2009;Tournaye et al, 2017) were selected for meta-analyses (TABLE 1). Notable exclusions (see Supplementary Table for complete list) included a sub-study (Yang et al, 2020) and a single-group trial with no control group (Nadarajah et al, 2017). Importantly, the retrospective case-control study that reported a link between dydrogesterone and cardiac abnormalities was excluded due to the high risk of bias, including the follow-up design that was based on patient recall of drugs used during a telephone call (Zaqout et al, 2015), and the non-peer-reviewed article that reported a link between dydrogesterone and fetal abnormalities (Koren and Gilboa, 2020) was excluded due to it being based on data from a publication that was retracted by the journal owing to errors and inconsistencies in the study design and statistical analysis (Koren et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, six RCT (Chan et al, 2021;El-Zibdeh, 2005;El-Zibdeh and Yousef, 2009;Griesinger et al, 2018;Pandian, 2009;Tournaye et al, 2017) were selected for meta-analyses (TABLE 1). Notable exclusions (see Supplementary Table for complete list) included a sub-study (Yang et al, 2020) and a single-group trial with no control group (Nadarajah et al, 2017). Importantly, the retrospective case-control study that reported a link between dydrogesterone and cardiac abnormalities was excluded due to the high risk of bias, including the follow-up design that was based on patient recall of drugs used during a telephone call (Zaqout et al, 2015), and the non-peer-reviewed article that reported a link between dydrogesterone and fetal abnormalities (Koren and Gilboa, 2020) was excluded due to it being based on data from a publication that was retracted by the journal owing to errors and inconsistencies in the study design and statistical analysis (Koren et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, in Lotus II studies, the mean body mass index was 23.1±3.1 vs . 23.1±3.0 kg/m 2 for DYD and MVP gel groups, respectively, while in ours, the average body mass index was 27.7±3.3 and 27.3±5.1 kg/m 2 , respectively [ 23 ].…”
Section: Discussionmentioning
confidence: 82%
“…A recent study of the categorized population in China observed a variation of 9.4% favoring DYD. However, current conception frequencies at the gestation age of 12 weeks of 61.4% and 51.9% for DYD and MVP gel arms, respectively, were observed [ 23 ]. Our finding on the ongoing conception rate was lower than the two groups (26.4% for the DYD group vs .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a phase-III randomized controlled trial (lotus II) compared oral Dydrogesterone (30 mg daily) with 8% MVP gel (90 mg daily from the day of ovum pick up until the 12 th wk of gestation). They concluded that oral Dydrogesterone had the same efficacy and safety as MVP gel and can be a good choice for LPS (37). Because Dydrogesterone is a more convenient route with good tolerability, it has been approved for use in LPS in several countries.…”
Section: Oral Progesteronementioning
confidence: 99%